Propriedades, negritude e moradia na produção da segregação racial da cidade: cenário Belo Horizonte - Lisandra Mara Silva (2018)
The objective of this study is to discuss the place of land ownership in the production of the city's racial segregation. It begins with theoretical research on the idea of private property constituted in the European historical-social processes - the right of a property - that spreads in the globe with the colonizing modernity becoming the primary symbol of capitalism. Also, we will investigate theories on racism to subsidize analyzes on strategies of coping with racism and in how it operates in the production of the city and at the same time as it shares space with the blackness. There will be the development of different analyzes, focused on empirical data obtained from interviews and institutional research; these analyzes will be based on theories such as analytical-conceptual elements about the production of urban space, microphysics of power and power in structures: the contributions of Santos, Bourdieu, and Foucault respectively. Thus, in the history of Belo Horizonte - created to be the whitest city of the Republic, in a colonized country at the periphery of global capitalism - the black population, its most substantial populational contingent, remains invisible from official historiography. From the formation of the first favelas to the recent urban occupations of land areas, power relations and their compulsory illegality are observed as a condition of access to urban land by the city's mostly black workers. Legal property - established in the field of the dispute of the right as the hegemonic form of wealth - constitutes an instrument of racism while the compulsory illegality constitute the condition of race, by institutionalizing the legal versus the illegal. Along with other precariousness reserved for the poor in the city, this condition is faced through the struggle for rights strengthened by networks of solidarity, the protagonism of women and the blackness. It is understood, therefore, the invisibility and the compulsory illegality as some of the forms of manifestation of the functional racism to the legitimation of the socioeconomic inequalities; it is structural racism that reifies in the segregated city and is produced by it in the socio-spatial dialectic.